PUPUK KANDANG DIPERKAYA FOSFAT ALAM DALAM BENTUK GRANULAR DAN DIINOKULASI BIODEKOMPOSER UNTUK MENINGKATKAN NUTRISI JERAMI JAGUNG MANIS SEBAGAI HIJAUAN PAKAN LOKAL DI LAHAN KERING - Dwi Retno Lukiwati; Endang Dwi Purbawati; Retno Iswarin Pujaningsih (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2015)
Manure enriched with rock phosphate (RP) and inoculated with biodecomposer very important to improve the dry land fertility. The objective of the research was to investigate the influence of some kind of manure enriched with RP in granular form and biodecomposer inoculated on sweet corn (Zea mays saccharata) stover nutrient as local forage feed for ruminant. A field experiment of completely randomized design with 7 treatments and four replicates was conducted on vertisol soil. Level of P (RP), N (urea) and K (KCl) fertilizers was 66 kg P/ha, 200 kg N/ha, and 125 kg K/ha, respectively. All of manure application at 30 t/ha, and enriched with RP. The treatments were T0 (manure), T1 (manure+EM4), T2 (manure+starTmik), T3 (manure+stardec), T4 (manure granular+EM4), T5 (manure granular+starTmik), and T6 (manure granular+stardec). The sweet corn was harvested at 70 days after planting, the stover was cut and measured for crude protein (CP), phosphorus (P), and calcium (Ca) concentration. The result showed that the treatment significantly affected to the nutritive value of sweet corn stover. The result of DMRT showed that effect of some kind of manure enriched with RP was not significantly different on CP, P, and Ca concentration of sweet corn stover. Conclusion, manure enriched by RP with or without biodecomposer, in granular or non-granular form, resulted in similar on CP, P, and Ca concentration of sweet corn stover.Keywords: biodecomposer, manure, phosphorus, stover, Zea mays saccharata.